2018
DOI: 10.1113/ep086809
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactic hypotension causes renal and adrenal sympathoexcitaion and induces c‐fos in the hypothalamus and medulla oblongata

Abstract: We previously reported that sympathetic nerve activity (SNA) to the kidney and the hindlimb increases during anaphylactic hypotension in anaesthetized rats. Based on this evidence, we examined effects of anaphylactic hypotension on SNA to the brown adipose tissue (BAT), and the adrenal gland and kidney in anaesthetized rats. We demonstrated that adrenal and renal SNA, but not BAT-SNA, were stimulated. In addition, the effects of anaphylaxis on neural activities of the hypothalamic and medullary nuclei, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
2
6
1
Order By: Relevance
“…The afferent vagal signals were conveyed to the NTS in the medulla oblongata. Furthermore, the increased c-Fos expression in the NTS during anaphylaxis (27) was abolished by vagotomy (3). Supporting this finding, we newly found that afferent vagal signals, but not afferent sympathetic signals from the stomach, increased during anaphylactic hypotension.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The afferent vagal signals were conveyed to the NTS in the medulla oblongata. Furthermore, the increased c-Fos expression in the NTS during anaphylaxis (27) was abolished by vagotomy (3). Supporting this finding, we newly found that afferent vagal signals, but not afferent sympathetic signals from the stomach, increased during anaphylactic hypotension.…”
Section: Discussionsupporting
confidence: 72%
“…We (24,25,27) previously reported that efferent sympathetic nerve activity to the kidney, hindlimb, and adrenal glands increased during anaphylactic hypotension in anesthetized rats. Here, we newly found that ef-GSNA increased during anaphylaxis, although the increase was limited to the early phase (1-10 min after antigen injection).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previously, we have shown that the hypothalamic AMPK also regulates leptin-induced renal sympathoexcitation and blood pressure elevation in rats (6,14). The efferent sympathetic signal to the kidney is a baroreceptor reflex-related nerve that responds to sodium nitroprusside-induced hypotension (20). Gastric SNA (10) and splenic SNA (data not shown) also increased during hypotension after sodium nitroprusside injection.…”
Section: Discussionmentioning
confidence: 69%